MENINGKATKAN HASIL BELAJAR LOMPAT JAUH MELALUI PERMAINAN LOMPAT GELANG-GELANG PADA SISWA KELAS V SDN 02 GARUNGWIYORO (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
This study is the limited infrastructure available in schools both in quantity and quality due to less supported by the level of ability, creativity and innovation, the operator of physical education teachers, especially in developing learning modelsDoes the game approach jump rings can know jauh.Tujuan increase learning outcomes expected jump was to determine Improved Learning Outcomes through the Long Jump Jump Games bangles. This study uses a classroom action research. Instruments used in collecting data obtained from the test results shown student performance during the implementation of the test. Data analysis was done descriptively comparative aimed to compare the conditions before and after the learning corrective action is held. From the results of research conducted, an increase in student learning outcomes from initial conditions to cycle 1 and cycle 2, both from an increase in the average value of the initial conditions (74.06), the average cycle 1 (75.75) and the average average cycle 2 (77.13) so that the increase from baseline to 2 cycles of (3.07%). Increased learning ability in the long jump motion can be seen from the KKM (75) or completed at 28.12%, after the action on the first cycle of students who pass the value of learning as much as 17 of the 32 (53.12) in cycle 2 which memeiliki value above KKM many as 26 students from 32 students overall or completed by (81.25%).